2010
DOI: 10.1002/hep.23905
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hepatitis B surface antigen decline during 3 years of telbivudine treatment in hepatitis B e antigen-positive patients

Abstract: The impact of prolonged direct antiviral therapy on hepatitis B surface antigen (HBsAg) levels in patients with chronic hepatitis B is poorly understood. We quantitatively assessed serum HBsAg levels during 3 years of telbivudine treatment, as well as their relationship with virologic and biochemical characteristics in 162 hepatitis B e antigen–positive patients who maintained undetectable serum hepatitis B virus (HBV) DNA long‐term. Telbivudine treatment progressively reduced serum HBsAg levels (mean ± SD) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
163
5
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 33 publications
(39 reference statements)
10
163
5
2
Order By: Relevance
“…A number of recent studies have suggested that monitoring HBsAg levels during treatment with a finite course of PEG-IFN may help identify those patients who are most likely to achieve a sustained response to therapy and go on to clear HBsAg (3,4,14,17,19) or identify those who may relapse following treatment (17). Recent data have also suggested that HBsAg levels may help predict response to therapy with NAs (9,25). For example, in analyses of patients treated as part of the pivotal trials of PEG-IFN alfa-2a in HBV, a decline of Ն10% in HBsAg levels from baseline at weeks 12 and 24 of treatment in HBeAg-negative patients (18) or HBsAg levels of Ͻ1,500 IU/ml at weeks 12 and 24 of treatment in HBeAg-positive patients (19) were found to be associated with high rates of sustained immune control and HBsAg loss posttreatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have suggested that monitoring HBsAg levels during treatment with a finite course of PEG-IFN may help identify those patients who are most likely to achieve a sustained response to therapy and go on to clear HBsAg (3,4,14,17,19) or identify those who may relapse following treatment (17). Recent data have also suggested that HBsAg levels may help predict response to therapy with NAs (9,25). For example, in analyses of patients treated as part of the pivotal trials of PEG-IFN alfa-2a in HBV, a decline of Ն10% in HBsAg levels from baseline at weeks 12 and 24 of treatment in HBeAg-negative patients (18) or HBsAg levels of Ͻ1,500 IU/ml at weeks 12 and 24 of treatment in HBeAg-positive patients (19) were found to be associated with high rates of sustained immune control and HBsAg loss posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the degree and timescale of reductions in HBsAg levels during pegylated interferon (PEG-IFN)-based therapy may predict a sustained response in both HBeAg-positive and HBeAg-negative CHB infection (3,11,13,14,17,19) and may also predict the response to treatment with some nucleos(t)ide analogs (NAs) (9,25). There is also evidence that HBsAg levels, particularly in combination with HBV DNA levels, can be used to identify patients who are in the inactive carrier phase of HBV infection compared with patients with active disease and so distinguish those patients who do not require therapy from those who would benefit from treatment (2,10,15).…”
mentioning
confidence: 99%
“…An HBsAg decline more than 1 log 10 IU/mL after 1 year of oral antiviral treatment in HBeAg-positive CHB patients have been shown to predict the HBsAg loss [32].…”
Section: Response-guided Therapy Based On Serum Hbsag and Hbv Dna Kinmentioning
confidence: 99%
“…Moreover, there is a variability of the quantitative HBsAg across different viral genotypes [3]. Patients with genotype A and D have the highest mean value of serum HBsAg (4.5 log 10 IU/mL) compared to genotypes B and C (4.3 log 10 IU/mL and 3.8 log 10 IU/mL, respectively) [32,39].…”
Section: Defining Different Phases Of Chbmentioning
confidence: 99%
“…Recently, evidence has suggested that the HBsAg levels change during the natural course of chronic HBV infection (8,9), and a rapid decline in HBsAg levels indicates a strong response to therapy, regardless of the treatment approach. Monitoring HBsAg levels can help identify nonresponders to therapy (peginterferon [PEG-IFN] or nucleoside analogues) and determine the best management strategy for many patients (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%